Egzystencjalne i ekonomiczne wymiary „czynnościowania” Zofii Kulik i jej matki Heleny - Agata Jakubowska (Miejsce)
The text analyses Zofia Kulik’s two films that form the cycle ”Cultivating the Archive: How the Sum Total of Small Actions Builds the Archive” (2016) and ”A Sum of Rags and an Archive Next Door, the Kingdom of Helena Kulik, Zofia’s Mother, in which the Archivist Grew Up” (2017). Both interweave two themes: work and the mother – daughter relation.